2010
DOI: 10.4103/0973-1075.73642
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial issues in palliative care: A review of five cases

Abstract: Palliative care is not just vital in controlling symptoms of the patient’s disease condition, but also aims to extend the patient’s life, giving it a better quality. However, several times in the course of management, the psychosocial impact of cancer, HIV/AIDS, and other life-limiting disease conditions may not be noticed and dealt with during the admission period, thereby giving rise to a more complex situation than the disease condition itself. This article aims to review some psychosocial issues and measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 29 publications
1
20
0
1
Order By: Relevance
“…Thus we had a final list of 90 articles for our analysis. [1112131415161718192021222324252627282930313233343536373839404142434445464748495051525354555657585960616263646566676869707172737475767778798081828384858687888990919293949596979899100]…”
Section: Resultsmentioning
confidence: 99%
“…Thus we had a final list of 90 articles for our analysis. [1112131415161718192021222324252627282930313233343536373839404142434445464748495051525354555657585960616263646566676869707172737475767778798081828384858687888990919293949596979899100]…”
Section: Resultsmentioning
confidence: 99%
“…Regarding inpatient social activities, we routinely hold multiple purposeful activities for patients, including patients' birthday parties, festival celebrations, and well‐wishing activities, because it has been found that these psychosocial care‐related activities can elevate the self‐esteem of patients, cultivate insight into adaptation to an illness and its outcome, and improve patients' relationships with their friends and families …”
Section: Discussionmentioning
confidence: 99%
“…Also, attention should be paid to the culture of parents as well (116). Raising public awareness concerning palliative care to overcome cultural and social barriers can also be an important factor in palliative care acceptance by parents (117). Public perspectives toward palliative care is complex (118) and its change requires relevant knowledge (119).…”
Section: -Providing Educational Programs For the Family Changing Thmentioning
confidence: 99%